CYCP2;1 integrates genetic and nutritional information to promote meristem cell division in Arabidopsis - Peng, Linda; Skylar, Anna; Chang, Peter L; Bisova, Katerina; Wu, Xuelin (Developmental biology, 2014)
In higher plants, cell cycle activation in the meristems at germination is essential for the initiation of post-embryonic development. We previously identified the signaling pathways of homeobox transcription factor STIMPY and metabolic sugars as two interacting branches of the regulatory network that is responsible for activating meristematic tissue proliferation in Arabidopsis. In this study, we found that CYCP2;1 is both a direct target of STIMPY transcriptional activation and an early responder to sugar signals. Genetic and molecular studies show that CYCP2;1 physically interacts with three of the five mitotic CDKs in Arabidopsis, and is required for the G2 to M transition during meristem activation. Taken together, our results suggest that CYCP2;1 acts as a permissive control of cell cycle progression during seedling establishment by directly linking genetic control and nutritional cues with the activity of the core cell cycle machinery.
Keywords: proteiny huseníčku; Cell Division; semenáček; cyklin-dependentní kinasy; Cyclin-Dependent Kinases; Arabidopsis Proteins; cykliny; sacharosa; Homeodomain Proteins; proliferace buněk; regulace genové exprese u rostlin; Gene Expression Regulation, Plant; Arabidopsis; Transcriptional Activation; rostlinné geny; aktivace transkripce; Genes, Plant; Seedlings; Cell Proliferation; homeodoménové proteiny; Sucrose; Cyclins; meristém; Meristem; buněčné dělení